The Use of Social Media to Build a Positive Image for High Schools : Pemanfaatan Media Sosial untuk Pembentukan Citra Positif Sekolah Menengah Atas - Uddin, Adam Amir; Dharma, Ferry Adhi (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The increasing competition in the digital era necessitates a re-evaluation of public relations strategies for educational institutions. This study focuses on the application of Cyber Public Relations (CPR) as a critical tool for schools to maintain a positive brand image and attract prospective students. Knowledge Gap: While the importance of digital presence is widely acknowledged, there is a limited understanding of the specific CPR strategies that are most effective for secondary schools in a local context. Aims: This research aims to analyze the specific CPR strategies implemented by SMA Muhammadiyah 2 Sidoarjo (SMAMDA) to enhance its positive image through social media. Results: The findings indicate that SMAMDA’s effective use of Instagram, through influencer collaboration, supportive partnerships, and consistent production of daily activity content, has been instrumental in attracting new students. Novelty: This study provides a practical case example of how a high school can successfully leverage specific digital communication tactics to achieve measurable marketing and branding outcomes. Implications: The research concludes that a school’s positive image and brand recognition can be significantly improved through the strategic and effective implementation of CPR. Highlights : The study reveals that SMAMDA’s CPR strategy on Instagram, which includes collaborations and daily content, is effective. This approach successfully attracts new students and enhances the school’s positive image. The research concludes that effective CPR is crucial for schools to build brand recognition in the digital age. Keywords: Cyber Public Relations, School Branding, Social Media, Content Strategy, Customer Engagement